Analisis Entrepreneurial Orientation Dan Organizational Learning Terhadap Marketing Capability Pada Umkm Di Industri Keripik Pisang Kabupaten Pringsewu - Fatoni; Setiawan, Satria Desta (LPPM STIE KRAKATAU, 2023)
Marketing Capabilities are skills in the field of marketing that are the result of a process of knowledge accumulation and integration with values and norms developed through organizational processes. The problem in this study is that not many banana chip entrepreneurs are able to expand the marketing area to outside Pringsewu. they send products to Bandar Lampung to be processed and repackaged Therefore, a lot of added value is lost from the banana chip industry. The purpose of this study was to determine the effect of entrepreneurial orientation and entrepreneurial orientation on marketing capability, and the effect of entrepreneurial orientation and organizational learning together on marketing capability in UMKM’s in the Pringsewu Regency Banana Chip Industry. This study uses quantitative research methods Data collection using questionnaires and interviews. Data analysis using SPSS with t test, F test and correlation coefficient. The results of the analysis with the partial t test show tcount 6.281> t table 1.8595, then Entrepreneurial Orientation affects Marketing Capability, tcount 1.118 < t table 1.8595, then Entrepreneurial Orientation has no effect on Organizational Learning, know tcount 1.118 < t table 1.8595, then Organizational Learning has no effect on marketing capability. Based on the results of the F test, it shows that there is an influence between the variables of Entrepreneurial Orientation and Organizational Learning together on Marketing Capability.